The relationship between substance use and problem solving ability of nursing students - Duran, Songül (Journal of Dependence, 2017)
Objective: The aim of this study is to investigate the relationship between nursing students’ substance use status and problem solving skills.Methods: The research is planned as a sectional and analytical type of study. The sample consists of 115 students studying at Nursing Department of Bitlis Eren University Health College between the dates 10.05.2013 and 15.06.2013. The Personal information form and Problem Solving Inventory were used as data collection tool. Data was evaluated by percentage and Mann-Whitney U test analysis.Results: According to the nursing students’ statements, 33% ofthem used cigarettes and 12.2% of them had drug-using experience. In this study, smoking students’ row mean scores of Problem Solving Inventory and the subscales of “problem solving confidence” and “approach/abstinence” are higher than the non smoker students’ (p
Keywords: Substance abuse; problem solving; etiology of substance abuse